The Role Of New Communication Tools In Election Campaigns: June 2011 General Elections In Turkey - Çedikçi, Tuğçe; Fener, Tuğba (Medimond S R L, Via Maserati 5, 40128 Bologna, 00000, italy, 2012)
Technology covers more and more space day by day in every part of our lives and brings with it both advantages and disadvantages. In today's world when transfer of message is realized at the highest level as a result of new communication technologies, communication process has also started to change. With digitalization, new communication tools create new social interaction fields for political parties; individuals, institutions and even governments direct these advantages and disadvantages towards their own interest and want to create awareness with the help of new communication technologies. One of the most important processes of political communication is the political campaigns, especially in election periods. During these campaigns, both programs and discourses of political parties resemble one another. In line with the technological developments experienced in today's world with the effect of globalization, parties have started to develop different strategies in election campaigns and desire to differentiate themselves from similar ones. It is necessary to establish campaign strategies and find creative strategies to differentiate election campaigns. In this sense, new communication technologies provide new human-centered channels and thus, directly support the campaign process. In the research which will be carried out in this context, a literature study will be made about the new media used by political parties in election campaigns in 2011 Turkish General Elections and the findings will be put forward.
Keywords: election campaigns; digitalization; communication tools; seçim kampanyaları; dijitalleştirme; iletişim araçları